Use of Hypertonic Sodium Chloride Solution at Surgery under Extracorporeal Circulation - V. V. Lomivorotov; E. V. Fominsky; V. A. Nepomnyashchikh (Общая реаниматология)
The paper analyzes the data available in the references on different aspects of using hypertonic sodium chloride solution during surgery under extracorporeal circulation in cardiosurgical care. The hypertonic solution is shown to lower positive fluid balance in the perioperative period, to increase cardiac output with simultaneously decreased vascular resistance, to improve lung oxygenating function, and to normalize tissue blood circulation and neurological status in patients exposed to artificial perfusion. There is evidence for its effect on the immune system and capillary endothelium. It is suggested that it is necessary to study the effect of the hypertonic solution on the incidence of complications and death rates during surgery under extracorporeal circulation and it is proposed to use the solution under long-term extracorporeal circulation. Key words: hypertonic saline, sodium chloride, extracorporeal circulation.